2022
DOI: 10.1155/2022/4052208
|View full text |Cite|
|
Sign up to set email alerts
|

Wind Tunnel Testing and Validation of Helicopter Rotor Blades Using Additive Manufacturing

Abstract: This research paper aims to validate the aerodynamic performance of rotor blades using additive manufacturing techniques. Wind tunnel testing is a technique used to find the flow characteristics of the body. Computational fluid dynamics (CFD) techniques are used for aerodynamic analysis, and validation should be done using wind tunnel testing. In the aerodynamic testing of models, additive manufacturing techniques help in validating the results by making models easily for wind tunnels. Recent developments in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…The analysis showed that the CFD results slightly overestimated the experimental data obtained from the wind tunnel, with an average error of 10%. However, based on the criteria recommended in [32], it was deemed that the validation of the CFD modeling study was acceptable.…”
Section: Validation Of the Numerical Approach And Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis showed that the CFD results slightly overestimated the experimental data obtained from the wind tunnel, with an average error of 10%. However, based on the criteria recommended in [32], it was deemed that the validation of the CFD modeling study was acceptable.…”
Section: Validation Of the Numerical Approach And Experimental Approachmentioning
confidence: 99%
“…The analysis showed that the CFD results slightly overestimated the experimental data obtained from the wind tunnel, with an average error of 10%. However, based on the criteria recommended in [32], it was deemed that the validation of the CFD modeling study was acceptable. The numerical approach employed in this study validates that forward flight conditions create a scenario where the lift force appreciably surpasses that in hover cases by an average of 39.9%.…”
Section: Validation Of the Numerical Approach And Experimental Approachmentioning
confidence: 99%
“…The difference between these equations' successive solutions will be shown by the residual plot. In a CFD simulation, the residual measures the local imbalance of the conserved variable in each control volume [36][37][38]. Therefore, the wing model will have its particular residual value for every equation solved in each cell.…”
Section: Study Of Rectangular Wing Model Using Naca 6412 Airfoilmentioning
confidence: 99%
“…Therefore, it avoids the general k-ω problem that the model is highly sensitive to the inlet turbulence properties of the free stream. Researchers often merit the SST k-ω model high because of its good behaviour in adverse pressure gradients and separating flows[34][35][36].…”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%